Oxygen uptake during repeated-sprint exercise - McGawley, K.; Bishop, D. J. (Journal of Science and Medicine in Sport, 2015)
Objectives: Repeated-sprint ability appears to be influenced by oxidative metabolism, with reductions in fatigue and improved sprint times related to markers of aerobic fitness. The aim of the current study was to measure the oxygen uptake Math Eq during the first and last sprints during two, 5 × 6-s repeated-sprint bouts. Design: Cross-sectional study. Methods: Eight female soccer players performed two, consecutive, 5 × 6-s maximal sprint bouts (B1 and B2) on five separate occasions, in order to identify the minimum time (trec) required to recover total work done (Wtot) in B1. On a sixth occasion, expired air was collected during the first and last sprint of B1 and B2, which were separated by trec. Results: The trec was 10.9 ± 1.1 min. The Math Eq during the first sprint was significantly less than the last sprint in each bout (p < 0.001), and the estimated aerobic contribution to the final sprint (measured in kJ) was significantly related to Math Eq in both B1 (r = 0.81, p = 0.015) and B2 (r = 0.93, p = 0.001). In addition, the Math Eq attained in the final sprint was not significantly different from Math Eq in B1 (p = 0.284) or B2 (p = 0.448). Conclusions: The current study shows that the Math Eq increases from the first to the last of 5 × 6-s sprints and that Math Eq may be a limiting factor to performance in latter sprints. Increasing Math Eq in team-sport athletes may enable increased aerobic energy delivery, and consequently work done, during a bout of repeated sprints.